Substantiation of Typical Agricultural Areas As a Methodological Basis for the Development of Regional Machine Systems - E. V. Zhalnin; V. A. Zubina (Сельскохозяйственные машины и технологии)
It was shown that when developing regional systems of technologies and machines, it is important to take into account all natural agro-climatic conditions and production capabilities in each region’s agricultural sector.Research purpose To develop a methodology for substantiating typical agricultural territories in each agricultural region so that the calculation results obtained for this territory are then generalized for the entire region.Materials and methods The production potential of the region was monitored, the basic assessment criteria were statistically processed and typical agricultural territories were selected according to the minimum deviation of the criteria particular values for the individual regions from the average weighted values for the whole region. All target territories within the region were grouped into homogeneous samples according to the minimum criteria variance. An algorithm for the sequence of computational and logical operations was proposed. The territories were assessed according to three uniformity criteria: the minimum sum of ranks for the priority of each basic criterion, the number of priority basic criteria, and the comparative significance of each region production potential. For typical areas, it was proposed to perform computer calculations of technical support options.Results and discussion The calculations were performed for the Central Non-Black Earth Zone of the Russian Federation. The following basic criteria for the production resources of the regions were adopted: the total arable land, the number of tractors, tractor availability and capability, the number of agricultural organizations in the region, the area for sowing grain crops, vegetables, and planting potatoes. The monitoring of the production resources criteria revealed their uneven distribution across the region and the subsequent necessity to identify two or three typical agricultural territories.Conclusions An algorithm was proposed for selecting typical territories and agricultural organizations in the region based on the case of the Central Non-Black Earth Zone of the Russian Federation. Within this zone, Kostroma, Ivanovo, Bryansk, and Yaroslavl regions were identified as typical ones.